Binocular vision training for professional athletes - Kutzner, Benedikt; Ring, Matthias; Michelson, Georg (Ophthalmologe, 2022)
Background Optimal visual abilities including stereo acuity seem to be an important issue in sports. There is increasing evidence that stereo acuity can be sustainably improved by digital vision training even for people with good stereo acuity. Study design and test methods In this study 31 male and female tennis players (professionals, young professionals, coaches and former professionals) completed at least 6 training units each with 192 dynamic stereoscopic tasks (N = 1152) within 6 weeks including a 4-option test with different levels of difficulty on a 3D screen at a distance of 5 m. The parameter reaction time and correctness at 15-300 arcseconds was determined. For a more precise representation of the reaction time improvement as a function of the difficulty level, the parameter reaction time increase per stereo disparity reduction (ReST) was defined. Results Reaction time to 15 arcsecond stimuli significantly decreased from 3.9 s to 1.6 s (59%) as a result of digital vision training. The correctness at 30 arcsecond stimuli significantly increased by 23%. Discussion The observed improvement in reaction time during vision training did not result in decreasing correctness when answering the visual questions. This represents an overall improvement in stereo vision. Conclusion Dynamic visual training over 6 weeks improves stereoscopic performance including stereo acuity, response time and correctness.
CRIS-Team WoS Importer:2022-02-11

Dichoptic Binocular Vision Training Improved Stereo Vision in Top Athletes - Michelson, Georg; Kutzner, Benedikt; Mehringer, Wolfgang; Paulus, Jan; Ring, Matthias; Eskofier, Björn (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01